Expression of IgA Proteases by Haemophilus influenzae in the Respiratory Tract of Adults With Chronic Obstructive Pulmonary Disease - Murphy, Timothy F. (J Infect Dis, 2015)
Background. Immunoglobulin (Ig)A proteases of Haemophilus influenzae are highly specific endopeptidases that cleave the hinge region of human IgA1 and also mediate invasion and trafficking in human respiratory epithelial cells, facilitating persistence of H. influenzae. Little is known about the expression of IgA proteases in clinical settings of H. influenzae infection. Methods. We identified and characterized IgA protease genes in H. influenzae and studied their expression and proteolytic specificity, in vitro and in vivo in 169 independent strains of H. influenzae collected longitudinally over 10 years from adults with chronic obstructive pulmonary disease. Results. The H. influenzae pangenome has 2 alleles of IgA protease genes; all strains have igaA, and 40% of strains have igaB. Each allele has 2 variants with differing proteolytic specificities for human IgA1. A total of 88% of 169 strains express IgA protease activity. Expression of the 4 forms of IgA protease varies among strains. Based on the presence of IgA1 fragments in sputum samples, each of the different forms of IgA protease is selectively expressed in the human airways during infection. Conclusions. Four variants of IgA proteases are variably expressed by H. influenzae during infection of the human airways.